2012
DOI: 10.1080/09614524.2012.673556
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking orphanhood and vulnerability in Ethiopia

Abstract: 'Orphans' became a category of vulnerable children deserving special protection in the context of the global AIDS epidemic, and currently the notion of 'Orphans and vulnerable children', or 'OVC', dominates much of the policy for protecting children across sub-Saharan Africa. Analysis of survey and qualitative data from Young Lives in Ethiopia found that parental death does not guarantee the often assumed negative impacts on children's experiences, and that inequalities between children are greater along dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Indeed, interviews with adult relatives, religious and community leaders in rural areas suggested that young people who had lost their parents were rarely considered 'orphans', but rather were regarded as ordinary members of the extended family. Close, loving family relationships and continuity in living arrangements may help to reduce the potentially negative emotional and material impacts of parental death on young people, as research in other contexts has shown (Crivello and Chuta 2012;Evans and Becker 2009). Vital conjunctures: reconfiguring intergenerational care and familial responsibilities in different spatial and temporal contexts…”
Section: Vital Conjunctures: Emotional Responses To Parental Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, interviews with adult relatives, religious and community leaders in rural areas suggested that young people who had lost their parents were rarely considered 'orphans', but rather were regarded as ordinary members of the extended family. Close, loving family relationships and continuity in living arrangements may help to reduce the potentially negative emotional and material impacts of parental death on young people, as research in other contexts has shown (Crivello and Chuta 2012;Evans and Becker 2009). Vital conjunctures: reconfiguring intergenerational care and familial responsibilities in different spatial and temporal contexts…”
Section: Vital Conjunctures: Emotional Responses To Parental Deathmentioning
confidence: 99%
“…The vulnerability of orphaned children compared with non-orphaned children in Africa has been increasingly questioned (Meintjes and Giese 2006). For example, while parental death impacted on children's educational outcomes and psychosocial well-being in Ethiopia, the quality of children's care relationships with family members and their economic security were more significant factors (Crivello and Chuta 2012). Hewlett's (2005) study among Aka and Nganda adolescents in the Central African Republic emphasises the need to understand the socio-cultural meanings of age, gender and family relations in young people's responses to death.…”
Section: Introduction: Youth Life Transitions and Parental Deathmentioning
confidence: 98%
“…Still, orphans remain a prime focus. In a review of UNICEF publications from the years 1996 to 2010, Crivello and Chuta (2012) found that the number of publications tagged as "orphan" rose from 2 publications in 1996 to 610 in 2010. In George, the addition of vulnerability made few waves in services, which were already minimal, and mostly filled by nongovernmental organizations.…”
Section: Childhood Tuberculosismentioning
confidence: 99%
“…25. See Ansell (2016), Crivello and Chuta (2012), and Meintjes and Geise (2006). To address funding gaps, the category has been broadened to orphans and vulnerable children, or OVC.…”
Section: Childhood Tuberculosismentioning
confidence: 99%
See 1 more Smart Citation